PENGUJIAN EFEK HIPOKOLESTEROLEMIA MINUMAN REBUSAN DAUN SALAM YANG MENGANDUNG EKSTRAK KAYU MANIS SECARA IN-VIVO PADA TIKUS PERCOBAAN (Testing The Hypocholesterol Effects of Drink of Boiled Bay Leaf Stew Containing Cinnamon Extract In-Vivo in Experimentals - Humaira Arifah Zahra; Elisa Julianti; Era Yusraini (Universitas Sumatera Utara, 2019)
ABSTRACT Functional drinks of boiled leaf water by adding cinnamon extract that has been reported has activity to reduce cholesterol levels. This research was conducted to determine the effect of the addition of cinnamon extracts in functional drinks decoction of bay leaf on the quality and consumer acceptance and also in decreasing of blood cholesterol levels of rats. This research was consisted of 2 (two) steps i.e: making functional drinks of boiled leaf water by adding cinnamon extract and testing the effect of hypocholesterol with boiled bay leaf stew containing cinnamon extract in-vivo in experimental rats. The group of mice were given 5 treatments, namely the administration of aquadest, the provision of bay leaf decoction drink with the addition of cinnamon extract of 100, 200, and 300 mg, and the provision of a comparative preparation of gemfibrozil dose of 21.6 mg/200 g b/day. The result showed that rat group that treated with cinnamon extracts dose 300 mg showed the most excellent treatment in decreasing of total cholesterol and LDL cholesterol in blood rats and being able to increase HDL cholesterol in rat blood within 14 days treatment although its ability is still below the rat group that treated with gemfibrozil dose of 21,6 mg/kg bw rat. Keywords: Hypercholesterolemia, Cinnamon, Cinamic Acid, Flavonoids, Bay leaves Decoction. ABSTRAK Minuman rebusan daun salam yang mengandung ekstrak kayu manis diketahui mengandung senyawa biokimia flavonoid dan asam sinamat yang dikenal memiliki aktivitas menurunkan kadar kolesterol. Penelitian ini dilakukan untuk mengetahui pengaruh penambahan ekstrak kayu pada minuman fungsional rebusan daun salam terhadap penurunan kadar kolesterol darah tikus. Penelitian ini terdiri dari 2 (dua) tahap yaitu pembuatan minuman fungsional air rebusan daun salam dengan penambahan ekstrak kayu manis dan pengujian efek hipokolesterol dengan minuman rebusan daun salam yang mengandung ekstrak kayu manis secara in-vivo pada tikus percobaan. Kelompok tikus diberikan 5 perlakuan yaitu pemberian akuades, pemberian minuman rebusan daun salam dengan penambahan ekstrak kayu manis 100, 200, 300 mg, dan pemberian sediaan pembanding gemfibrozil dosis 21,6 mg/200 g bb/hari. Hasil penelitian menunjukkan bahwa kelompok tikus dengan pemberian dosis 300 mg ekstrak kayu manis memiliki kemampuan paling baik dalam menurunkan kadar kolesterol total dan kolesterol LDL darah tikus dan mampu meningkatkan kadar kolesterol HDL darah tikus selama 7 hari walaupun masih di bawah kelompok tikus dengan pemberian gemfibrozil 21,6 mg/ 200 g bb tikus. Kata kunci: Hiperkolesterolemia, Kayu Manis, Asam Sinamat, Flavonoid, Rebusan Daun Salam.